2021
DOI: 10.3389/fvets.2021.741210
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Galectin-3 Evaluation in Dogs With Cardiac and Non-cardiac Diseases

Abstract: Galectin-3 is involved in important biological functions such as fibrogenesis and inflammation. Notably, it is associated with various diseases and plays a major role in cardiac inflammation and fibrosis. Although heart diseases are relatively common in dogs, a few studies have analyzed the circulating galectin-3 concentration in dogs with various heart diseases, including myxomatous mitral valve disease, patent ductus arteriosus, and pulmonic stenosis. The aims of the present study were to evaluate the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Although, previously, a significantly positive correlation was found between Gal-3 and NT-proBNP and Gal-3 was shown to have predictive potential for diastolic dysfunction, Gal-3 cannot be designated either as an MMVD- or as a cardiac-specific marker. Increased values of circulating Gal-3 were previously reported for various diseases, for example, endocrine and dermatologic diseases as well as cancer [ 24 ]. Nevertheless, the inhibition of Gal-3 with modified citrus pectin, an emerging heart failure therapy for dogs, resulted in the reduced burden of reactive interstitial fibrosis in CHF and reduced and preserved ejection fraction [ 25 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although, previously, a significantly positive correlation was found between Gal-3 and NT-proBNP and Gal-3 was shown to have predictive potential for diastolic dysfunction, Gal-3 cannot be designated either as an MMVD- or as a cardiac-specific marker. Increased values of circulating Gal-3 were previously reported for various diseases, for example, endocrine and dermatologic diseases as well as cancer [ 24 ]. Nevertheless, the inhibition of Gal-3 with modified citrus pectin, an emerging heart failure therapy for dogs, resulted in the reduced burden of reactive interstitial fibrosis in CHF and reduced and preserved ejection fraction [ 25 ].…”
Section: Discussionmentioning
confidence: 95%
“…Increased concentrations of circulating and tissue Gal-3 directly correlate with macrophage migration/activation and development of myocardial fibrosis in human and murine as well as with advancement of canine MMVD. Previously, it was demonstrated that, in human and canine MMVD, the concentrations of circulating Gal-3 correlate with the amount of collagen accumulated in the heart, the incidence of CHF, and disease progression and outcome [ 19 , 22 , 23 , 24 ]. Our results ( Figure 1 ) further confirm previous experimental findings and identify the Gal-3 marker as a potentially important mediator of myxomatous degenerative changes in both asymptomatic and symptomatic stages in canine MMVD.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of right atrial volume may provide clinically relevant information regarding RV diastolic function, and measurement of right atrial area may have provided a more precise evaluation of the right atrial dimension compared to the linear variable used in our study. Additionally, circulating Gal-3 has been found to be increased in dogs with noncardiac diseases such as severe dermatologic disease including neoplasia 66,67 and endocrine disease, 66 as well as in cirrhosis of the liver in human patients. 68 In experimental studies of animals with cardiac disease and in studies of humans without the above-listed diseases, concentrations of Gal-3 correlate well with the degree of myocardial fibrosis observed.…”
Section: Discussionmentioning
confidence: 99%